Produksi Biodisel Berbasis Minyak Nabati Menggunakan Aspen HYSYS - Firda Dimawarnita; Afifah Nur Arfiana; Sri Mursidah; Syarifah Rohana Maghfiroh; Prayoga Suryadarma (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
Biodiesel is a mono-alkyl ester derived from fatty acids that produced from vegetable oil or animal fat. It is known to be environmentally friendly, does not pollute the air, easily biodegradable, and can be renewed. Therefore, biodiesel has great prospects to be developed in overcoming the limited oil production. Esterification of fatty acids contained in vegetable oil is one way to produce biodiesel. Then, transesterification process separates glycerin from vegetable oil. Based on SNI 7182: 2015, the minimum yield standard for biodiesel is 96.5%. That high yield standard is a challenge in designing the biodiesel production process. In addition, the yield optimization process generally inflicts higher costs and energy. Therefore we need a biodiesel production process design for optimization. Optimization process must consider the composition of the material, the type of reaction, the type of reactor, and the material stream in order to produce the higher yield of biodiesel. This paper aims to optimize biodiesel production through process simulation. The expected biodiesel product is methyl oleate (C19H36O2) with triolein (C57H104O6) as feed. Simulations were carried out using the HYSYS software for three different scenarios. The simulation results are expected to provide an overview of the design of the biodiesel production process that can meet the yield standard and energy efficiency. Based on the three simulated scenarios, the 3rd scenario was chosen as the best biodiesel production process with a yield of 96.5%. In addition, the heat exchanger is used to help reduce the energy requirement from outside the system. [Keywords: biodiesel, production optimization, vegetable oil, hysys